2012
DOI: 10.1007/s00446-012-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic information dissemination in mobile ad-hoc networks: the profit of global synchrony

Abstract: The topic of this paper is the study of information dissemination in mobile ad-hoc networks by means of deterministic protocols. We assume a weak set of restrictions on the mobility of nodes, parameterized by α, the disconnection time, and β, the link stability time, such that the mobile ad-hoc networks considered are connected enough for dissemination. Such a connectivity model generalizes previous models in that we assume much less connectivity, or make explicit the assumptions in previous papers. The protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It was also observed that random graphs, as used in previous experimental studies [13], reduce the convergence time, and therefore are not a good choice to indicate worst-case behavior. These experiments showed good behavior even for networks that sometimes are disconnected, indicating that more relaxed models of dynamics, such as (α, β)-connectivity [14,15], are worth to study.…”
Section: Previous Workmentioning
confidence: 90%
“…It was also observed that random graphs, as used in previous experimental studies [13], reduce the convergence time, and therefore are not a good choice to indicate worst-case behavior. These experiments showed good behavior even for networks that sometimes are disconnected, indicating that more relaxed models of dynamics, such as (α, β)-connectivity [14,15], are worth to study.…”
Section: Previous Workmentioning
confidence: 90%
“…These experiments showed good behavior even for networks that sometimes are disconnected, indicating that more relaxed models of dynamics (e.g. [14,15]) are worth studying.…”
Section: Previous Workmentioning
confidence: 90%
“…It was also observed that random graphs, as used in previous experimental studies [12], reduce the convergence time, and therefore are not a good choice to indicate worst-case behavior. These experiments showed good behavior even for networks that sometimes are disconnected, indicating that more relaxed models of dynamics, such as (α, β)-connectivity [13,16], are worth to study. All in all, the experiments in [6] showed that Incremental Counting behaves well in a variety of pessimistic inputs, but not having a proof of what a worst-case input looks like, and being the experiments restricted to a range of values of n far from the expected massive size of an Anonymous Dynamic Network, a theoretical proof of polynomial time remained an open problem even from a practical perspective.…”
Section: Anonymous Dynamic Networkmentioning
confidence: 99%